CHEMICAL DESICCANTS FOR ANTICIPATION OF HARVEST AND PHYSIOLOGICAL QUALITY OF COWPEA SEEDS - Raisse, Elizeth Regina (2020)
Information about the effect of herbicides on cowpea seed quality is scarce. The objective of this work was to evaluate the effect of using chemical desiccants at pre-harvest on the anticipation of harvest and physiological quality of cowpea seeds of the cultivar BRS-Tumucumaque, before and after storage. Two experiments were conducted: experiment 1 was conducted under a randomized block design, with four replications; the treatments consisted of seven herbicides (carfentrazone-ethyl, saflufenacil, glyphosate, paraquat, flumioxazin, glufosinate-ammonium, and diquat) and a control treatment; anticipation of harvest, and seed water content, germination, and vigor were evaluated. The seeds were stored for six months in controlled environment and not-controlled environment rooms and evaluated for water content, germination, and vigor in Experiment 2, which was conducted in a 7×2+1 factorial arrangement, with four replications; the first factor consisted of the seven herbicides, the second factor was the two storage environments, plus a control treatment. The results showed 3 to 9 days of anticipation of harvest relative to the control. The glufosinate-ammonium herbicide negatively affected seed germination and vigor. The glyphosate herbicide decreased seed germination and vigor after storage. The physiological quality of cowpea seeds at the post-harvest period and after six months of storage was not affected by the carfentrazone-ethyl and flumioxazin herbicides. Paraquat and diquat were the most efficient herbicides for the anticipation of harvest (nine days). Glyphosate and glufosinate-ammonium were the most harmful herbicides to seed physiological quality. The controlled environment room was the most adequate environment for seed conservation.